Oral Microbial and Biofilm Changes in Response to Clear Aligners: A Scoping Review - Ricky Cho; Beatriz Panariello (Oral Sphere Journal of Dental and Health Sciences, 2026)
Despite the growing use of clear aligners in orthodontics, their impact on oral microbial ecology and biofilm formation remains uncertain. The aim of this scoping review is to summarize the existing evidence on the impact of clear aligners on oral microbiome composition, biofilm development, and plaque accumulation during orthodontic treatment. Original research studies, including both in vitro and clinical investigations, published between 2015 and 2026 were eligible. PubMed, EBSCOhost, and Google Scholar were searched using predefined keywords. The review protocol was registered in the Open Science Framework. Data was extracted and descriptively synthesized to summarize study characteristics, outcomes, and key findings. Nineteen studies met the inclusion criteria. Clear aligners were generally associated with improved gingival indices and reduced bleeding compared with fixed appliances. However, findings regarding plaque accumulation and microbial composition were inconsistent. Some studies reported lower plaque scores among aligner users, whereas others found no significant differences or higher plaque levels, particularly in cases of inadequate oral hygiene or prolonged wear. Microbiome analyses demonstrated shifts in microbial communities in both aligner and fixed appliance groups, with aligners not consistently preventing dysbiosis. In vitro studies showed that aligner materials can support biofilm formation, influenced by material properties and cleaning protocols. Current evidence suggests that clear aligners do not consistently prevent plaque accumulation or microbial dysbiosis; therefore, their presumed hygienic superiority should not be assumed. This review highlights the need for improved patient compliance and hygiene education to reduce microbial imbalance and plaque accumulation in clear aligners users.